Model Dakwah Fardiyah Tarekat Qodiriyah wa Naqsabandiyah - Suherdiana, Dadan (Jurnal Ilmu Dakwah, 2009)
Daâwah can be done withÂ  model medley,Â  one of it namedÂ  ad-daâwah fardiyah that was done by tarekat Qadiriyah wa naqsabandiyahs fellow men. Unique characteristic of model it lays in mention or greeting in the context relationship between them; mursyids call to teachers, sheikh for tarekats founder, murid for what do bailing knowledge, ikhwan for each member. Naming or use of greeting word purpose is not pointless even have particular implication to attitude, interaction and teaching pattern between them.